Conductive hearing loss in large vestibular aqueduct syndrome —clinical observations and proof-of-concept predictive modeling by a biomechanical approach. (July 2021) - Pang, Jia; Wang, Yanmei; Cheng, Yushu; Chi, Fanglu; Li, Yike; Ni, Guangjian; Ren, Dongdong
Abstract: Objective: The purpose of this study was to investigate the effect of a dilated vestibular aqueduct on conductive hearing loss (CHL). A biomechanical method was proposed for modeling the patterns of CHL in patients with large vestibular aqueduct syndrome (LVAS). Study design: High resolution computed tomography (CT) scans and pure tone audiometry (PTA) were retrospectively collected from 16 patients who were diagnosed with LVAS. Seventeen ears with measurable air-bone gaps (ABGs) on PTA were applied for model development. The sizes of midpoint, operculum and distal segment were measured from CT to calculate the biomechanical parameters of each vestibular aqueduct. The mechanical effect of the dilated vestibular aqueduct on sound conduction was simulated using a lumped-parameter model. The CHL levels predicted by the model were compared with the observed ABGs at 250, 500 and 1000 Hz respectively. Results: The model was able to predict the trend that greater ABGs occurred at lower frequencies, which were consistent with clinical observations. However, deviations between the predicted and the observed ABGs became larger as the frequency increased. None of the correlation coefficients between the radiologic measures and the observed ABG levels were significant. Conclusion: These findings lend support to the feasibility of this approach in modeling CHL in LVAS. The presence of a dilated vestibular aqueduct leads to altered impedance and sound pressure, suggesting the impact of a pathological third window. High individual variability of the observed ABGs implies additional factors may also be involved, especially at 500 Hz and 1000 Hz.